A longitudinal case study of six children with autism and specified language and non-verbal profiles. (4th May 2022) - Miniscalco, Carmela; Carlsson, Emilia
ABSTRACT: Language skills as well as general cognitive skills show a considerable variation in children with autism spectrum disorder (ASD). In previous studies, at least three profiles based on these skills have been suggested; autism with language and non-verbal cognitive skills within the average/normal range (ALN), autism with language disorder (ALD) without concurrent non-verbal cognitive disability, and autism with language disorder and cognitive disability, i.e. autism with a more general delay (AGD). The aim of the present longitudinal case study is to illustrate these three groups more thoroughly by presenting the developmental trajectories of children belonging to each profile. Six children were chosen based on their language and cognitive profiles from the first age 3-year assessment. They came from a larger group of children with ASD identified by autism screening at child health-care centres at age 2.5 years. These six children represent one boy and one girl from each of the three subgroups ALN, ALD and AGD, and were assessed a second time at age 5 and a third time at age 8 years, regarding expressive and receptive language skills, autistic severity and non-verbal cognitive skills. Although preliminary, our results indicate a rather stable developmental trajectory from age 3 to 8 years characterising children with autism based on language and non-verbal cognitive functioning. Thus, in order to help intervention planning and increase predictions of outcome, it seems important to specify both linguistic and cognitive level already at the first assessment in children with ASD.